Horizontal Saccadic Velocity in Patients with Exotropia before and after Unilateral Resection and Recession Surgery - Miharu Mihara; Atsushi Hayashi; Kazuya Fujita; Ken Kakeue; Ryoi Tamura (Journal of Ophthalmology)
Purpose. The effects of strabismus surgery on eye movement are not known in detail, as few studies have compared saccade velocities before and after strabismus surgery. In this study, horizontal saccades were recorded using an eye-tracker in patients with only exotropia to compare the peak velocities (PVs), before and after undergoing strabismus surgery of the same type (unilateral resection and recession). Methods. Horizontal saccades of monocular vision were recorded using an eye-tracking device in 18 patients with exotropia and 20 normal subjects. All patients were examined using the same method after strabismus surgery. Results. The PVs of adduction and abduction in the patients were higher than those in the normal subjects (in dominant eye, P=0.032 for adduction and P=0.049 for abduction; in nondominant eye, P=0.016 for adduction and P=0.037 for abduction). Following the surgery, the PVs of abduction of the surgical eye (nondominant eye) decreased to the level of the normal subjects (P=0.016). However, there were no correlations between changes in the PVs and the extent of surgery (resection and recession). Conclusion. Strabismus surgery normalized the patient’s increased PV in the operated eye for abduction of horizontal saccade. Not only peripheral (extraocular muscle) but also central sensory-motor mechanisms may be involved in the changes in PV of horizontal saccades, both of which could result from the improvement of the primary eye position.